Crosstalk between the gut microbiota and innate lymphoid cells in intestinal mucosal immunity - Guo, Yuling; Liu, Yujia; Rui, Binqi; Lei, Zengjie; Ning, Xixi; Liu, Yinhui; Li, Ming (Frontiers in Immunology, 2023)
The human gastrointestinal mucosa is colonized by thousands of microorganisms, which participate in a variety of physiological functions. Intestinal dysbiosis is closely associated with the pathogenesis of several human diseases. Innate lymphoid cells, which include NK cells, ILC1s, ILC2s, ILC3s and LTi cells, are a type of innate immune cells. They are enriched in the mucosal tissues of the body and have recently received extensive attention. The gut microbiota and its metabolites play important roles in various intestinal mucosal diseases, such as inflammatory bowel disease (IBD), allergic disease, and cancer. Therefore, studies on ILCs and their interaction with the gut microbiota have great clinical significance owing to their potential for identifying pharmacotherapy targets for multiple related diseases. This review expounds on the progress in research on ILCs differentiation and development, the biological functions of the intestinal microbiota, and its interaction with ILCs in disease conditions in order to provide novel ideas for disease treatment in the future.